O ENSINO DE ADMINISTRAÇÃO DA UNIJUÍ: QUATRO DÉCADAS DE HISTÓRIA - Enise Barth Teixeira (Universidade Federal de Santa Catarina, 2013)
The present article aims rescue and describe the history of forty years of the Administration course at Unijuí, situated at the city of Ijuí/RS. The development of this study is based in the analysis of historical documents and perceptions of three pioneers professors, exploring the memories, mainly the most striking aspects along this path. The research ranks as qualitative-explorative. The study of case constitutes on the strategy of investigation. The technical procedures used were bibliographical, documental and empirical research. The semi-structured interview was the utilized technique for the empirical data collect. The study results show the challenges and difficulties faced, as well as relevant facts lived along the four decades of Administration education of Unijuí. The resumed history of the Administration course viewed by the pioneer docents and historic documents are lined of great importance on the memory of this graduation during its timeline, ensuring thus the information storage and its meanings. The history, beyond the past recover, allows a better comprehension of present and so can design the future of the Administration education and its contribution on the sustainable regional development.